(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2020)
Profound changes in requirements and demands of new skills and competences in the field of labour, which are preconditioned by significant technological development, changing economies, social and political establishments, place educational systems throughout the world (especially vocational education and training and adult education) ahead of a major challenge. – How to enable individuals to gain the skills and competences needed for the labour market of the future? Accomplishing this ambitious goal means that it is necessary to change the old paradigm of “job for a life time” to the new paradigm “learning throughout life” or “lifelong learning”. Non-formal education in the context of lifelong learning concept is one of the paths that ensures equal opportunities for obtaining relevant skills, attitudes and competences among individuals. It is compensating the disadvantages of the formal education system which adapts too slowly to the socio-economic changes and is characterized with conservatism leading to inertia of the societies themselves. This paper tends to present educational offer and inclusion in non-formal adult education area, analysing the educational programme offer on one hand, and inclusiveness of the process of non-formal education on other hand. Results will point out the good practices, as well as the challenges that will need to be addressed urgently in order to accomplish the goal of inclusion and equity in the context of lifelong learning concept.